Knowledge, Attitude, and Practice toward Probiotics Among the General Adult Population in Malaysia - Kyaw, Thin Mon; Mike Chin Weng Kit; Nursufiah Nabilah Binti Hasrin; Hessiya Vidhya Radhakrishnan; Harshitha Shivashankara; Rosemaria Diana Binti Mohammad Ayub; Ng Just Ruiy; Naganathan Kathiresan Pillai (Diyala Journal of Medicine, 2025)
Background: Probiotics are live microorganisms that, when consumed or applied in sufficient amounts, bring health benefits to the host, according to the definition by the International Scientific Association for Probiotics and Prebiotics. Objectives: This study aimed to explore the association between the understanding, beliefs, and behaviors of the Malaysian adult population regarding probiotics. Patients and Methods: A cross-sectional study was carried out using convenience sampling technique among the general adult population in Malaysia, within a duration of 6 weeks during 2024, to explore how the understanding, beliefs, and behaviors of the adult population related to probiotics were associated with their awareness of the potential health benefits. Results: Among 397 adults, the mean (±SD) scores were 10.2 ± 3.5 for knowledge, 5.1 ± 1.0 for attitude, and 6.0 ± 1.9 for practice. Overall, 32.0% had good knowledge, 89.7% positive attitudes, and 65.7% good practices. Most respondents (over 95%) recognized the benefits of probiotics, and 78.3% reported prior consumption. Multivariate logistic regression showed that Malaysian females were more likely to have good knowledge (AOR = 1.76, 95% CI: 1.14–2.70, p = 0.010). Malay ethnicity was associated with more favorable attitudes (AOR = 4.29, 95% CI: 0.80–23.00, p = 0.049), while Malaysian nationality was linked with lower odds of good practices (AOR = 0.69, 95% CI: 0.38–0.92, p = 0.019). Conclusion: To gain the potential benefits of using probiotics for overall health and well-being, more studies are needed to fully understand their mechanisms and optimal applications. As our knowledge of microbiomes expands, so does the potential for probiotic interventions in supporting overall well-being. Keywords: Knowledge, Attitude, Practice, Probiotic usage, Malaysia.